A Student Mobility Program through Cross Cultural and Technical Exposure - Ito, Teruaki; Mohamad, Effendi; Salleh, Mohd Rizal (2013)
The University of Tokushima (UT) and Universiti Teknikal Malaysia Melaka (UTeM) have concluded an academic partnership under the agreement of MOU/MOA in 2013. As one of the academic joint activities for the agreement, a mobility program was initiated at UTeM (MMPT2013) and the mobility students of UTeM joined the CEL Summer Program (CELSP) at UT in 2013. First this paper shows the selection process of the mobility students at UTeM. Then, the paper presents the overview of CELSP designed for the mobility students with four subprograms including cultural experience, academic activities, robotic projects, and manufacturing projects. Then the paper shows the various activities of mobility students in CELSP and explains how they have learned the basic approach of design using deterministic design method. The concluding section discusses the outcome of the CELSP program.